Global prevalence and predictors of scabies among prisoners: systematic review and meta-analysis - Amare Mebrat Delie; Eyob Ketema Bogale; Tadele Fentabel Anagaw; Misganaw Guadie Tiruneh; Eneyew Talie Fenta; Ousman Adal; Natnael Kebede (BMC, 2024)
Abstract Introduction Scabies is a widespread issue in prisons due to overcrowded living conditions and limited healthcare resources. A recent study published in the Journal of Infection and Public Health discovered that the prevalence of scabies varies greatly among prisoners in different regions and facilities. This review aimed to determine the global prevalence and predictors of scabies among prisoners by conducting a systematic review and meta-analysis. Methods We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis checklist to report the findings of our systematic review and meta-analysis. Relevant databases including PubMed, Cochrane Library, ScienceDirect, and other grey literature databases were used to search and retrieve articles. The study included both published and unpublished research written in English languages for studies reporting the prevalence of human scabies among prisoners. This review has been registered on PROSPERO. The heterogeneity of the data was evaluated using the I2 statistic. A meta-analysis was conducted using STATA 17 software, with a 95% confidence interval. The researchers also conducted publication bias and sensitivity analysis. Results The review included 7 studies involving 1, 309,323 prisoners. All included studies involved cross-sectional study design. The prevalence of scabies among prisoners ranges from 0.72% in Italy to 41.01% in Cameroon. The global pooled prevalence of human scabies among prisoners was found to be 6.57% (95% CI; 2.16-19.94). According to subgroup analysis, the overall prevalence of scabies among African prisoners was 19.55% (95% CI; 9.44-40.45), while the prevalence among prisoners outside of Africa was 1.57% (95% CI; 0.77-3.19). The length of time spent in prison, sharing of clothing or beds, and hygiene practices were found to be factors that were significantly associated with the likelihood of prisoners developing human scabies. Conclusion The overall prevalence of human scabies is high among prisoners worldwide. Prisoners who spent more time in prison shared clothing or beds, and had poor hygiene practices were more likely to develop human scabies. Thus, efforts should be made by policymakers and program administrators to decrease the prevalence of scabies in prisons. The protocol for this systematic review and meta-analysis was registered in the International Prospective Register of Systematic Reviews with registration number CRD42024516064.